A prospective observational study evaluating the short-term effectiveness of residential care for adolescents as “service as usual”: A study protocol - Pia K. Eriksson; Elina Aaltio; Mikko Aaltonen; Taina Laajasalo (PLoS ONE, 2026)
Previous research indicates worse outcomes for children and young people in out-of-home care compared to their peers. To improve the quality of current residential care, research is needed to deepen our understanding of the key factors and mechanisms that explain the effectiveness of residential care on child level. The aim of this study is to evaluate the short-term (i.e., during care) effectiveness of residential care as a child welfare intervention by different service providers. The study includes two pre-specified primary child-level outcomes 1) psychosocial functioning, assessed through the Strengths and Difficulties Questionnaires (SDQ) including both total difficulties scores and subscales and 2) attainment of individual goals of the child. Secondary outcome measures include improved experiences of emotional warmth and safety (CEWSS-A). Further associations between key characteristics of the residential care unit, the child and outcomes are assessed. The data consist of longitudinal survey data collected from 12–17-year-old children and staff in a total sample of public and private residential care units offering specialized care in three wellbeing services countries in Finland. The baseline (T0) data is collected between 1.4.2025–31.8.2026 with a follow up of 6 and 12 months for each child (T1 and T2). The data is primarily analysed with linear mixed models. Findings explore the short-term effectiveness and change mechanisms of residential care as “service as usual” to understand how it should be organised and produced to improve its ability to meet aims during care. The study design embraces the complexity and changeability on different levels of the residential care setting.